The circuit of detachment in Chile : understanding the fate of a neoliberal laboratory - Araujo, Kathya (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
"This Element discusses the consequences for the social bond of the conjoint action of the economic and social model inspired by the premises of neoliberalism and of the powerful pressures for the democratization of social relations in Chilean society. It is based upon empirical research developed in the past fifteen years. The main argument in this Element is that these processes have had as one of their most important effects the generation of a circuit of detachment, that is, a process that leads to different forms of disidentification and distancing from logics and principles that govern social relations and interaction. It is a dynamic circuit consisting of four components: excess, disenchantment, irritation, and, finally, detachment. The Element analyzes this circuit and each of its components as well as its consequences for the social bond. It also includes a brief reflection on the impact of this circuit on the political bond"--
Sisältää bibliografisia viitteitä.
Keywords: uusliberalismi; poliittinen osallistuminen; sosiaalinen muutos; demokratisoituminen; Neoliberalism -- Chile; Democratization -- Social aspects -- Chile; Social change -- Chile; Political participation -- Chile; Chile; Chile -- Politics and government -- 1988-